Identification and mechanistic analysis of neurovascular coupling related biomarkers for diabetic macular edema - Chen, Tianpeng; Sheng, Shufan; Chen, Jing; Wang, Xiaole; Shang, Yanxing; Duan, Chengwei; Liang, Caixia; Song, Yu; Zhang, Dongmei (Frontiers in Molecular Biosciences, 2024)
Diabetic macular edema (DME) is a major cause of vision loss in the sick with diabetic retinopathy. The occurrence of DME is closely related to the breakdown of neurovascular coupling; however, its underlying mechanism has not been fully elucidated. The aim of this study was to investigate the diagnostic biomarkers and potential molecular mechanisms associated with neurovascular coupling in DME. Using differential gene expression analysis, STEM, and WGCNA from GSE160306, Neurotrophic factor receptor (NGFR) was identified as a hub gene related to neurovascular coupling and DME. The expression of NGFR was verified by RT-qPCR in vitro cells. GSEA analysis indicated that high expression of NGFR may affect immunity and inflammatory pathway, thereby regulating neurovascular coupling and mediating the development of DME. The NGFR co-expression network was constructed, which exhibited the correlation with the neurotrophin signaling pathway. Moreover, a diagnostic model for DME based on NGFR and PREX1 was constructed using LASSO regression analysis and nomogram, which were validated through AUC values and the C-index, demonstrating relatively good diagnostic performance. To briefly conclude, the high expression of NGFR may lead to abnormal neurovascular coupling and participate in the occurrence of DME by regulating the immunity, inflammatory and neurotrophin signaling pathway. Detection of NGFR and related expression genes may be beneficial for monitoring the occurrence and development of DME.